The Effect of Employee Development Policy, Work Environment, and Transformational Leadership on Employee Creativity in Indonesia's Creative Industries - Loso Judijanto; Tera Lesmana; Agung Zulfikri (Westscience Press, 2024)
This research investigates the impact of employee development policy, work environment, and transformational leadership on employee creativity within Indonesia's dynamic creative industries. A quantitative analysis employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was conducted to analyze data collected from 120 employees across various sectors of the creative industry. Descriptive statistics, measurement model assessment, structural model analysis, and hypothesis testing were employed to examine the relationships between the variables of interest. The results reveal that employee development policy, transformational leadership, and work environment significantly influence employee creativity within Indonesia's creative industries. Specifically, organizations that prioritize employee development, foster transformational leadership behaviors, and provide supportive work environments are more likely to enhance employee creativity. These findings underscore the importance of organizational strategies and leadership practices in fostering a culture of innovation and creativity within Indonesia's burgeoning creative economy.